Effects of pressure drop on supercritical fluid chromatography. - Lim, Lenard Junming. (2009)
This project investigates the effects of pressure drop on the physical properties changes of supercritical carbon dioxide in a chromatography column. Axial temperature measurements of the chromatography column were made with surface type thermocouples. The chromatography column is insulated with a cotton layer and kept in a Styrofoam container, and the entire chromatography column and insulation are housed within an oven. It is found out experimentally that the axial temperature change of CO2 decreases along the chromatography column.